Use of computers and applications by senior executives - Josep Lluís Cano-Giner (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: Analyze the relationship between the senior executive and ICT use. Design/methodology/approach: Empirical research through which we propose a framework to establish the main factors that might lead to an increase in ICT use by senior executives. Findings: The main contribution of the present study is the creation of the list of factors that affect the use of computers and applications by senior executives and a smaller group of categories. Research limitations/implications: A limitation of this research is that it should be confirmed by means of quantitative research that would allow us to test the validity of the proposed framework, and also to ascertain the relative importance of each factor. Practical implications: Thus reducing the number of factors and forming a smaller group of categories that can facilitate research. Originality/value: The list of factors that affect the use of computers and applications by senior executives and the smaller group of categories.
Keywords: 650; senior executive; users; information and communication technologies; executive information system